Micromineral status of soil, salt-tolerant plants and goats in tidal estuarine ecosystem of Indian Sundarban - GHOSH, SARBASWARUP; MUKHERJEE, JOYDIP; SAHA, MONIDIPTA; ROY, KRISHNENDU; SAHU, NARAYAN CHANDRA; HAZRA, ALOK KUMAR (The Indian Journal of Animal Sciences, 2019)
It could be concluded that tidal coastal zones contain high level of micro-minerals in soil and plants. Paradoxically, local goats inhabiting in this particular ecosystem are deficient in Fe, Cu and Mn. This might be an adaptive response of animals in that area. Tanins are well-known inhibitor of Fe absorption from intestine. Regular consumption of tanins and other plant alkaloids during grazing and browsing might also be responsible for low bio-availability of the minerals in the plasma. Further research is warranted to have more insight on mineral status of small ruminants in fascinating ecosystem of Sundarbans.